2015
DOI: 10.1002/cmdc.201500471
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine Triazole Thioether Derivatives as Toll‐Like Receptor 5 (TLR5)/Flagellin Complex Inhibitors

Abstract: Protein-protein interactions have been regarded as "undruggable" despite their importance in many biological processes. The complex formed between host toll-like receptor 5 (TLR5) and flagellin, a globular protein that is the main component of a bacterial flagellum, plays a vital role in a number of pathogen defenses, immunological diseases and cancers. Through high-throughput screening, we identified two hits with a common pharmacophore, which were used to successfully develop a series of small-molecule probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Control experiments confirmed that TH1020 also inhibited flagellin-induced TLR5 activation in HEK-hTLR5 cells as reported previously (Yan et al, 2016) with no apparent cytotoxicity (Figure S2G). Furthermore, NF-κB activation was inhibited by treating HMGB1 stimulated HEK-hTLR5 cells with triptolide, a small molecule inhibitor of NF-κB (Qiu et al, 1999) (Figure 2E).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Control experiments confirmed that TH1020 also inhibited flagellin-induced TLR5 activation in HEK-hTLR5 cells as reported previously (Yan et al, 2016) with no apparent cytotoxicity (Figure S2G). Furthermore, NF-κB activation was inhibited by treating HMGB1 stimulated HEK-hTLR5 cells with triptolide, a small molecule inhibitor of NF-κB (Qiu et al, 1999) (Figure 2E).…”
Section: Resultssupporting
confidence: 89%
“…First, an anti-TLR5 NAb was used to block direct activation by flagellin or HMGB1, followed by a small molecule inhibitor of MyD88 (Davis et al, 2006) and a peptide inhibitor of the TIRAP pathway (Brown and McIntyre, 2011) to target the downstream adaptor proteins (Figure 2). Finally, two more inhibitors, triptolide (NF-κB inhibitor) (Qiu et al, 1999) and TH1020 (TLR5 inhibitor) (Yan et al, 2016) were applied to decipher how the HMGB1-TLR5 signaling activates the NF-κB-driven proinflammatory pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the upregulation of TLR 5 and -8 correlated with the increase in IL-17C production in both the porcine intestinal tissues and IPEC-J2 cells upon F4 + ETEC stimulation, in a next effort we wanted to determine which TLR controls IL-17C expression in IECs upon ETEC infection. Given the fact that TLR5 engagement elicits the expression of IL-17C in human IECs [23], we further elucidated IL-17C expression in the presence of the TLR5 signaling inhibitor TH1020 [22] and oligodeoxyribonucleotides (ODN) 2088, which inhibit TLR7/8/9 signaling [20, 21]. As TH1020 and ODN 2088 were dissolved in DMSO and TE buffer, respectively, the effect of these two solvents on IL-17C production by IPEC-J2 monolayers was also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Two hours before bacterial inoculation, IPEC-J2 monolayers were incubated with 0.5 μM oligodeoxyribonucleotide (ODN 2088, Miltenyi Biotec, Bergisch Gladbach, Germany; blocks TLR7/8/9 signaling as described previously [20, 21]), TH1020 (SML1741, Sigma-Aldrich, inhibits TLR5 signaling as described previously [22]), 20 or 40 ng/mL IL-17C (MyBioSource, San Diego, CA, USA) and then inoculated for 24 h with the different bacterial strains as described above. As flagellin has been reported to induce IL-17C production in several epithelial cells [7, 23, 24], IPEC-J2 monolayers were also stimulated with flagellin (100 ng/mL, FLA-ST Ultrapure, Invivogen, San Diego, CA, USA) in the presence or absence of TH1020.…”
Section: Methodsmentioning
confidence: 99%